How far away is Europe? Institutional development in Europe's Balkan and Black Sea neighbours - Rainer Schweickert (Intereconomics, 2004)
Institutional development in new and potential member countries determines the success of deepening European integration. This papers argues that the timing of future enlargement should depend on institutional convergence between the EU and potential accession candidates. It therefore looks at institutional quality in the EU, in the EU's neighbouring Balkan and Black Sea regions, and especially in Bulgaria, Romania, Croatia, and Turkey, i.e. the next countries in the queue for entry. Three dimensions of institutional quality – legislative, administrative and judicial institutions – are analysed on the basis of the World Bank Governance Indicators using institutional quality in EU member states as a benchmark in order to reveal institutional deficits.
Keywords: 330; Institutioneller Wandel; Institutionelle Infrastruktur; Systemkonvergenz; EU-Erweiterung; Europäische Integration; Südosteuropa; Schwarzes Meer